Postmelting Encapsulation of Glass Microwires for Multipath Light Waveguiding within Phosphate Glasses - Konidakis, Ioannis; Dragosli, Foteini; Cheruvathoor Poulose, Aby; Kašlík, Josef; Bakandritsos, Aristides; Zbořil, Radek; Stratakis, Emmanuel (ACS applied optical materials, 2024)
Glass waveguides are the fundamental component of advanced photonic circuits and play a pivotal role in diverse applications, including quantum information processing, light generation, imaging, data storage, and sensing platforms. Up to date, the fabrication of glass waveguides relies mainly on demanding chemical processes or on the employment of expensive ultrafast laser equipment. In this work, we demonstrate an advanced, simple, low-temperature, postmelting encapsulation procedure for the development of glass waveguides. Specifically, silver iodide phosphate glass microwires (MWs) are drawn from splat-quenched glasses. These MWs are then incorporated in a controlled manner within transparent silver phosphate glass matrices. The judicious selection of glass compositions ensures that the refractive index of the host phosphate glass is lower than that of the embedded MWs. This facilitates the propagation of light inside the encapsulated higher refractive index MWs, leading to the facile development of waveguides. Importantly, we substantially enhance the light transmission within the MWs by leveraging the plasmon resonance effects due to the presence of silver nanoparticles spontaneously generated owing to the silver iodide phosphate glass composition. Employing this innovative approach, we have successfully engineered waveguide devices incorporating either one or two MWs. Remarkably, the dual MW devices are capable of transmitting light of different colors and in multipath direction, rendering the developed waveguides outstanding candidates for extending the functionalities of diverse photonic and optoelectronic circuits, as well as in intelligent signaling applications in smart glass technologies.